Pengujian Black Box Sistem Penjualan Minimarket Sodaqo Berbasis Website Menggunakan Teknik Equivalence Partitions - Raudhatul Zannah; Astalia Putri Yuniasih; Hadi Suparman; Ichsan Muhamad Kamal; Umirah; Ahmad Fauzi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The minimarket sales system has become an integral part of the modern retail industry. In an effort to improve efficiency and customer satisfaction, many mini-markets have turned to web-based solutions. This study aims to test the Sodaqo website-based minimarket sales system using the black box testing method with the equivalence partitioning technique. Black box testing is a software testing method in which testing is carried out without regard to the internal structure or implementation details of the system. Meanwhile, equivalence partitioning is a testing technique that divides input into equal or equivalent groups to reduce the number of test cases that must be tested. The test results show that the website-based Sodaqo minimarket sales system functions properly and meets the predefined functional requirements.